PENGARUH FAKTOR PSIKOLOGIS TERHADAP KEPUTUSAN PEMBELIAN DALAM TRANSAKSI E-COMMERCE - Raharjanti, Rani; Mardinawati, M.; Ardiansah, M. Noor; Hidayati, Ulfah; Susena, S. (Manajerial : Jurnal Manajemen dan Sistem Informasi, 2020)
The aim of this research is to analyze and to test about the psychological effect toward purchase decision e-commerce transaction. The sample of this research were Computerized Accounting study program’s student of Politeknik Negeri Semarang. Purposive sampling was used on this research. Data was collected from students through questionnaires. We used multiple linear regression model on this research. The result was concluded that the trust variable proved have a positive influence towards purchasing decisions in e-commerce transactions, meaning that the higher of the level of trust, the higher the purchasing decision in e-commerce transactions. While service quality and risk perception are empirically proven have no influence on e-commerce purchasing decisions. This is because consumers feel that almost every e-commerce has the same quality of service and risk management, so consumers are no longer too worried about these two problems. Keywords: psychology factor; e-commerce; buying decision; trust; service quality